Nurettin Topçu’nun eğitim anlayışında öne çıkan değerler - Şahin, Sümeyye (My University, 2011)
Small and medium sized enterprises have ability to create renewal, doing international businesses gives them a chance to contribute the economy of the country. Also their flexible constructions, ability of quick and easy adaptions on changes at the bazaar almost gives them dinamic and important place in economies of all the countries. Small and medium sized enterprises, have faced lots of serious difficulties and disadvantages during the export processes but also they provide lots of contribution on the economics of developed and developing countries during the export processes. The goal of this study is, to find out the difficulties, during their export processes between different attributed furniture manufacturer companies and the furniture manufacturer companies which have different export levels, in İstanbul. 92 furniture manufacturer companies attend this survey. The survey results showed that some of the detection levels on difficulties of export processes depends on the atributes of companies. Key Words: SMEs, Export, Export Barriers
Keywords: Din Eğitimi; Eğitim